SCIENTIFIC APPROACHES TO THE CONCEPT «MOTIVATION» AS A PEDAGOGICAL AND PSYCHOLOGICAL PROBLEM - DEMCHENKO, Inha (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
This article is about the problem of students’ motivation for learning. In the article the problem of motivation, structure of motivation is considered, the concept of the term «motivation», «motivation of educational activity» is disclosed, the author gives the definition of the term «motivation». The motives of educational activity and methods of motivation are analyzed in the work, which should contribute to increase the effectiveness of educational activity.